2016
DOI: 10.3892/ol.2016.4585
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography analysis of benign and malignant nodules in patients with chronic lymphocytic thyroiditis

Abstract: Abstract. The aim of the present study was to compare the multidetector computed tomography (MDCT) features of benign and malignant nodules in patients with chronic lymphocytic thyroiditis (CLT). MDCT findings, including the size, solid percentage, calcification, margin, capsule, anteroposterior-transverse diameter ratio as well as the mode and the degree of enhancement of 137 thyroid nodules in 127 CLT cases were retrospectively analyzed. Furthermore, the correlation between MDCT findings and pathological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…Although a larger size has been reported as an independent predictor of malignancy [3,37,41], the relationship between nodule size and risk of thyroid cancer remains uncertain. In concordance with the results of other studies [42][43][44][45], we observed that benign thyroid nodules were significantly larger than malignant nodules, and that the risk of thyroid cancer was inversely related to the largest nodule diameter. Even more relevant, benign lesions were more frequently oval-shaped and parallel-oriented.…”
Section: Discussionsupporting
confidence: 92%
“…Although a larger size has been reported as an independent predictor of malignancy [3,37,41], the relationship between nodule size and risk of thyroid cancer remains uncertain. In concordance with the results of other studies [42][43][44][45], we observed that benign thyroid nodules were significantly larger than malignant nodules, and that the risk of thyroid cancer was inversely related to the largest nodule diameter. Even more relevant, benign lesions were more frequently oval-shaped and parallel-oriented.…”
Section: Discussionsupporting
confidence: 92%